Um senhorio originado pela Palavra do Senhor: estudo exegético do Salmo 110 - Barros, Paulo Freitas (2014)
The objective of this master s thesis is an exegetical analysis in which will be described the theological dimensions of Psalm 110. Based on philological studies of ancient Hebrew a new translation of this Psalm is presented, as literal as possible. The study covers the historical and cultural context of the Psalm 110 as well as the theological thoughts related to the king and the Lord, God of Israel. Through the principle of canonical exegesis, the study includes the observance of parallels between biblical texts, which explain each other. Psalm 110 will also be researched within the texts of the New Testament, thereby demonstrating its importance for the reflection about Jesus Christ